Personal Protective Equipment (PPE) and Nurses’ Anxiety During the Covid-19 Pandemic - Juwi Athia Rahmini; Sri Dhamayani; Widyawati Widyawati; Martiningsih Martiningsih; Ai Cahyati; Dian Novita; Eka Budiarto; Amelia Arnis (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2023)
Anxiety felt by nurses is a vague fear accompanied by feelings of uncertainty, helplessness, isolation, and insecurity when performing nursing care during the Covid-19 pandemic. Nurses need personal protective equipment as a barrier against substance penetration, solid, liquid, or airborne particles to protect against injury or the spread of disease. The purpose of this study is to identify characteristics, length of work, PPE training, Psychologic services, PPE access, booster vaccination, standard PPE nurse anxiety and the correlation between PPE and anxiety on nurses in the COVID-19 room. This research is a quantitative study using a causal - comparative study design that is non-experimental (ex post facto). The sampling method used is purposive sampling technique approach with a sample of 90 respondents using data entry with demographic data sheet, PPE completeness checklist sheet to determine PPE completeness and to determine nursing anxiety using the Hamilton Anxiety Rating Scale questionnaire. Results showed the majority of nurses were middle-aged, woman, diploma, married, working more than 2 years, have participated in PPE training, not aware of access to psychological service, experienced easy accessibility of PPE, has not received a booster vaccine, using standardized PPE and experienced mild anxiety. This study shows that there is no significant difference in mean (p value> 0.05), which means that PPE training, psychological services, access to PPE, booster vaccinations, standardized PPE did not correlate to nurses’ anxiety. The government is expected to give intervention through policies to address nurses’ anxiety and factors related to this, such as providing effective counselling services.